A critical analysis of semiotic adaptations in postmodern cinema - Addley Bromeo Bianus; Imelda Ann Achin (Psychology and Education, 2021)
Modern cinema's role has been very influential in defining the new age art, especially the semiotic adaptations that have become more meaningful with the invention of modern technologies. Art has come a long way in the past few decades. The emotions are the same, but the expressions have changed. Literature has influenced the semiotics in modern cinema and has brought a new meaning to the characters' expressions in the stories. This paper would analyse the journey of semiotic adaptations in postmodern cinema. A detailed understanding of the factors responsible for it and the development over the past few years would help study the new-age films better. The research would focus on the semiotics in the old age films and compare it with the new age adaptations made in this field. The study would also include modern cinema developments worldwide and comprehensive insight into the adaptations worldwide.